Madrasah Effort in Improving the Quality of Teacher Work in the Mass of the Covid 19 Pandemic in Madrasah Aliyah Private PreparationFor the State of Besitang - Ziaulhaq, Wahyu (ASIAN PUBLISHER, 2022)
This study describes the efforts of the head of the madrasa in maintaining the quality of teacher work during the COVID-19 pandemic at the private preparatory madrasah aliyah in Besitang. The purpose of this research is to educate teachers so that they always evaluate the quality of teacher work so that the quality of work quality remains optimal in the mass of the Covid 19 outbreak. This research is a type of qualitative research that seeks to explain social phenomena that are developing in the current mass. The data collection techniques he did were observation and unstructured interviews and then the data were analyzed objectively and then described scientifically by following the procedures for writing scientific papers. using digital technology. Give the task to the teacher to deliver material to students in accordance with the instructions that have been set by the government. The principal of the madrasa conducts periodic supervision by monitoring learning activities online and monitoring the list of student assessments in accordance with student competence. The head of the madrasa seeks to improve coordination with parents of students related to the implementation of student learning activities while at home. The head of the madrasa continues to conduct training for madrasa teachers so that madrasa teachers understand the procedures for making lesson plans and learning models by utilizing digital technology